The effect of thymol on acetylcholine-induced contractions of the rat ileum and uterus under ex vivo conditions - Premrov Bajuk, Blanka; Prem, Luka; Vake, Tilen; Žnidaršič, Neža; Snoj, Tomaž (Frontiers in Pharmacology, 2022)
Thyme (Thymus vulgaris L.) is a well-known medicinal plant, the aerial parts of which have long been used internally or externally as a traditional remedy for various diseases. Thyme essential oils have important pharmaceutical applications and are regularly used in the pharmaceutical, food and cosmetic industries. In folk medicine, thyme preparations are used to treat respiratory, digestive, cardiovascular and nervous disorders, as well as to relieve dysmenorrhea. Thymol, a major constituent of Thymus vulgaris essential oil, has been shown to affect skeletal and smooth muscle excitation and contraction. Therefore, the main objective of this study was to evaluate its effect on acetylcholine (ACh)-induced rat intestinal and uterine preparations. Isolated ileumsmall intestine and uterine horn preparations were placed in a 20-mL organ bath containing Tyrode or De Jalon solution and exposed to graded concentrations of ACh (0.036, 0.109, 0.36, 1.09, 3,6, 10.9, and 36 uM) and either 0.02 or 0.2 mM thymol. Additionally, the dose–response relationship of thymol impact on intestinal and uterine contraction was evaluated. Contraction changes were monitored using an isometric transducer. Thymol at the higher dose (0.2 mM) significantly reduced ACh-induced intestinal and uterine contractions. Thus, this study provides new important data on competitive actions between thymol and ACh. In the dose–response study, the IC50 values were calculated as 5.26 mM for the ileum and 5.35 mM for the uterus. Our results demonstrated the efficacy of thymol in reducing ileal small intestinal and uterine smooth muscle contractions, thus supporting the use of thyme in traditional medicine in the treatment of digestive disorders and painful menstrual cramps.